Keberlanjutan Rantai Nilai Komoditas Beras - Fitriani Fitriani; Cholid Fatih; Sutarni Sutarni; Fembriarti Erry Prasmatiwi (AGRIMOR, 2021)
Understanding the linkage of a product flows along the commodity chain is important as the starting point in determining a sustainability strategy. The scope of the rice commodity value chain in this study involves farmers' rice production, small-scale rice mills and the home industry of rice milling. The study aims to identify commodity chains of rice in Lampung Province. The primary data from the rice processing industry and rice trading using a questionnaire guidance. The purposive sampling method is used by considering the rice milling business's representation related to the commodity chain. Qualitative analysis of the pattern of relations between business actors carried out with the agri-food value chain approach. The pattern of chain starts from the process of transforming raw materials into the manufactured and the final product until it reaches the end consumers. The commodity chain involved the flow of production, information (price and marketing chain), and income flow. Generally, there are 3-5 rice flour milling units in the village, with a 50-120 kg/month production volume. The average price of rice flour is Rp. 12,500/kg. The ability to supply paddy grain for milling is 2-5 tons/agent/week. Rice mills generally have 2-6 suppliers of fixed paddy grain. Information on product flow diagrams includes product types, ease of obtaining goods, time dependence, and ease of selling goods. Information on paddy grain prices on the supplier line is an average of Rp 4,500/kg. The price of rice in the distribution line to the wholesale rice trader is Rp. 8,500. Meanwhile, the income stream provides information on the value of rice production revenue of 59.7 tons per month attaint to Rp 40.3 million with a profit amount of Rp 318/kg.